Selective biosorption of aurum(III) from aqueous solution using oil palm trunk (OPT) biosorbents: Equilibrium, kinetic and mechanism analyses - Saman, N. (Elsevier B.V., 2018)
The oil palm trunk (OPT) biosorbents (i.e. OPT-W, OPT-D and OPT-T) were prepared for the recovery of Au(III) from an aqueous solution. Simple preparation procedures were carried out to minimize the use of hazardous chemicals and reduce the preparation costs. The biosorbent characterization results show that the prepared OPT biosorbents have nearly similar morphological structure, surface area, porosity, net surface charge and functional groups. The highest Au(III) biosorption capacity of 91.47 mg gâ1 was observed for the OPT-D followed by OPT-T (75.30 mg gâ1) and OPT-W (74.11 mg gâ1). The Au(III) isotherm data fitted well with the Langmuir model, while the Au(III) kinetic data were well described by the pseudo-second order model. The mechanisms for the Au(III) biosorption were governed by diffusional and chemical interaction mechanisms in which the film diffusion was the rate-controlling step. The chemical interaction via electrostatic and reduction mechanisms between Au(III) and biosorbent surface active sites played a significant role for Au(III) biosorption in acidic condition. The OPT-D showed a good selectivity towards Au(III) from the coexisting ions in aqueous solution. The OPT-D also shows better reusability potential towards Au(III) which indicates the potential applications of OPT biosorbents as low-cost biosorbents for the recovery of Au(III). The Au(III) can be recovered from the burning residues of the Au(III) loaded OPT biosorbents. Â© 2018